Potential of fortified spent mushroom substrate for the management of soil borne diseases of tomato - Arathikrishna V K (Department of plant pathology, College of horticulture, 2015)
Mushrooms are produced on natural materials taken from agricultural waste. SMS is the substrate left after harvesting of mushroom fruit bodies. SMS contains a diverse range of soil microorganisms. This is proven by its disease suppressing properties and its effectiveness in bioremediation. Additions of microorganisms to soil ultimately enhance and accelerate regular soil process such as nutrient mobilization. Among the beneficial uses of SMS the disease controlling property is quite interesting. Tomato is one of the most widely used vegetable. The bacterial wilt and damping off are the two serious soil borne diseases of this crop. The management of diseases using chemicals is not safer to environment due to residual problem. Increasing concern regarding food safety and environmental pollution has generated an interest in eco friendly practices like soil amendment and application of biocontrol agents to manage the plant diseases. Under these circumstances this study was taken up to assess nutritional and disease management aspects of fortified SMS in tomato The antagonists used for this study like Trichoderma hamatum, T. viride and Bacillus subtilis are the isolates from SMS obtained from the previous studies conducted in the Department of Plant Pathology along with reference cultures of Kerala Agricultural University viz. T. viride and Pseudomonas fluorescens. They were evaluated against major soil borne fungal pathogens like Pythium aphanidermatum, Phytophthora palmivora, Fusarium oxysporum, Rhizoctonia solani and Sclerotium rolfsii and bacterial pathogen Ralstonia solanacearum of tomato. The in vitro evaluation showed that T. hamatum was the best among three fungal antagonists. While in case of bacteria P. fluorescens was the best. A microbial consortium of these two organisms was also prepared. The selected best antagonists and consortium were applied to SMS @ 300 ml per kg and kept for biosoftening for 60 days. The fortified SMS with P. fluorescens softened the SMS to a certain level. The primary nutrients like N, P, K, secondary nutrient Ca and micro nutrient Cu were found to be decreased as the time increases. In the pot culture experiment for the management of damping off, the treatment SMS fortified with consortium gave maximum per cent inhibition against the disease. In the management of bacterial wilt also SMS fortified with consortium found to be best in disease suppression as well as plant growth promotion. All the treatments with SMS were found to posses disease management property and enhance the plant growth. From this study it is clear that fortified SMS paves a new way in disease management. For confirmative result, elaborative field study has to be conducted and the quality of SMS has to be worked out.